Improving English Speaking Proficiency for Secretarial Purposes through Task-Based Learning - Arifin, Zaki Zainal (SENTRI: Jurnal Riset Ilmiah, 2025)
This qualitative study investigated the effectiveness of Task-Based Learning (TBL) in improving English speaking proficiency among secretarial students with limited English skills. The research was conducted with 30 fourth-semester students enrolled in the Secretary Study Program at Pamulang University, who were identified as having low levels of English speaking ability. Through classroom observations, semi-structured interviews, and students’ reflective journals, the study explored how real-life task simulations such as telephone conversations, appointment scheduling, meeting arrangements, and business presentations impacted learners’ confidence, fluency, and functional language use. The findings indicate that TBL created meaningful and interactive speaking opportunities that helped students overcome their fear of speaking, promoted collaborative learning, and improved their ability to use English in job-specific contexts. Furthermore, the study revealed that when tasks were authentic and relevant to professional secretarial duties, students were more motivated to participate and take risks in speaking. The results suggest that incorporating TBL into English for Specific Purposes (ESP) instruction can significantly enhance the communicative competence of secretarial students preparing for workplace communication.